The role of sensor technology in sustainable and efficient agricultural production - Review - Sojnóczki, István; Bojtor, Csaba; Illés, Árpád; Nagy, János; Széles, Adrienn (Precision Crop Production, 2025)
Agricultural sensor technology has become a cornerstone of modern precision farming over the past two decades. Our research focused on the applications of remote and proximal sensing technologies, with an emphasis on satellite, drone-based, soil-embedded, and plant-mounted sensors. The study analyzed the presence of sensors in scientific publications and the evolution of research trends. The results showed that the number of scientific publications on sensor technology has grown exponentially, particularly in the last decade, reflecting increasing scientific and practical interest in the field. It was found that modern advancements, such as nanotechnology, have significantly contributed to reducing sensor size and enhancing their sensitivity, thereby supporting sustainable agricultural practices. Sensor applications enable the optimization of water, nutrient, and energy use, contributing to agricultural sustainability. Our research highlighted the importance of sensor technology in improving production efficiency and addressing global agricultural challenges.